Why get tested? Linking Intentions for Seeking SARS-CoV-2 Testing with RT-PCR Results and Cycle Threshold Values at Community Testing Sites. (28th October 2021) - Laitman, Andrew; Greninger, Alex; Mathias, Patrick; Hoffman, Noah
Abstract: During the SARS-CoV-2 pandemic, community-based testing sites have provided free COVID testing to millions of people who would have otherwise faced substantial barriers. In one metropolitan area, over 700, 000 tests were performed from September 2020 through February 2021. To make appointments online, people not only provided basic demographic information such as age, gender, and address but also free-text reasons for seeking testing. We sought to examine how reason for testing, coded as free text, in combination with other collected demographic information, correlated with rates of SARS-CoV-2 positivity and measures of infectiousness such as the Real-Time Polymerase Chain Reaction (RT-PCR) Cycle Threshold (Ct) value. Data from the scheduling software used to coordinate the on site testing workflow was extracted and linked to SARS-CoV-2 PCR assay metadata stored in a laboratory data warehouse, including Ct values. We categorized individual text responses into 3 separate categories: symptomatic, exposed but asymptomatic, and asymptomatic without exposure. Symptomatic individuals were identified based on the presence of common keywords and phrases like "symptom", "fever", "cough", and "sore throat." Similarly, exposed individuals were identified by keywords such as "exposed", "exposure", and "roommate." All others were categorized as asymptomatic. We found that symptomatic individuals had the highest frequency of testing positive at 11.6% (21, 150/181, 868). Exposed individuals and asymptomatic individuals had lower rates of detection with frequencies of 7.4% (10, 266/138, 721) and 4.9% (8, 987/185, 026) respectively. Repeat testing represented 29.9% of the results and positivity rates were calculated using the first result for each individual. In addition, among those who tested positive, symptomatic individuals exhibited the lowest average Ct values, while those who are asymptomatic exhibit the highest average Ct values. Among those who self-reported duration of symptoms, recent onset of symptoms was strongly correlated with lower Ct values. Across more than 700, 000 results, self-reported symptomatic people, based on free text responses, have a higher likelihood of testing positive for SARS-CoV-2. People who claim a more recent onset of symptoms are more likely to exhibit higher concentrations of viral RNA.